Community engagement through Library and Information Science teaching- learning activities at Islamic higher education in Indonesia - Labibah Labibah; Marwiyah Marwiyah; Nita Siti Mudawamah; Anindya Gita Puspita; Siwi Anjarwati (Berkala Ilmu Perpustakaan dan Informasi, 2023)
Introduction. Community engagement is one of the ways to connect between academic environment and community. This research aims to explore community engagement as part of the course in the Library Science Study Program to match with the seven main principles of community engagement. Research Method. This is qualitative research with a case study approach on how community engagement concept is implemented in the learning and teaching activities at UIN Sunan Kalijaga Yogyakarta and UIN Maulana Malik Ibrahim Malang. Data analysis. The data was analyzed by using cross-case data analysis. Results and Discussion. The results show that the two LIS Programs have conducted community engagement effectively in their learning and teaching by referring to the main seven principles of community engagement. Conclusion. In terms of the community engagement, UIN Malang has more intensive relationships with the community because their activities involve wider community around the area. While in terms of the sustainability, UIN Yogyakarta shows a better-organized program as they assign the students to create strategic plans and SOPs by encouraging the community library organizers to continue what has been conducted by the students during the program. This community engagement program also in line with community service missions of the university.